Korupsi dalam perspektif Islam dan budaya hukum - Sutrisno Sutrisno; Choirul Anam (AT-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Background. The practice of corruption in Indonesia is like an “illegal inheritance” without a will. Law enforcement and its enforcement are constantly evolving and adapting the actions, or types of corruption crimes that exist in society. The majority of corruptors are Muslims. Calculatively, Muslims are bigger than non-Muslims who are involved in corruption. Aim. This study aims to reflect eclectically on the problem of corruption in Indonesia from the perspective of Islam and legal culture. Methods. This research is a literature study (library research). Research data comes from books, scientific articles, journals, magazines and other sources relevant to the object of discussion. The research data were analyzed and conclusions were drawn descriptively-analytically. Results. Islam expressly condemns and curses thieves and looters of other people's property, except for the corrupt. The legal culture shows that corruption is influenced by individual and collective needs and demands, and is also supported by the socio-cultural environment that inherits the tradition of corruption. The government prioritizes the social, economic and political economic status of corruptors. The internal legal culture of law enforcement does not support resolving corruption in court proceedings.